2020
DOI: 10.6060/ivkkt.20206304.6096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ethyl Ether of 4(4-Hydroxyphenyl)- and 4′-Methyl-4(4-Hydroxyphenyl)cyclohexancarbonic Acids and Their Aminomethylated Derivatives

Abstract: The article presents the results of cycloalkylation of phenol with ethyl cyclohexane- and 4-methylcyclohexenecarboxylic esters in the presence of a zeolite-Y catalyst impregnated with phosphoric acid. It has been established that to perform the cycloalkylation of phenol with ethyl cyclohexenecarboxylic acid in the presence of a zeolite-Y catalyst impregnated with orthophosphoric acid, the optimal conditions are: temperature 120 °С, reaction time 5 h, molar ratio of phenol to ether 1 : 1 mol/mol. And amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Among a large number of petrochemical products, alkylphenols are widely used as initial reagents in the synthesis of fuel additives and stabilizers, inhibitors of freeradical oxidation of organic and bioorganic substrates, herbicides, fragrances, etc. [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a large number of petrochemical products, alkylphenols are widely used as initial reagents in the synthesis of fuel additives and stabilizers, inhibitors of freeradical oxidation of organic and bioorganic substrates, herbicides, fragrances, etc. [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it found that at a temperature of 80 °C, reaction t i m e o f 2 h , 1 : 2 : 2 m o l a r r a t i o o f palkylphenol to formalin and aniline, the yield of 2-hydroxy-5-alkylbenzylphenylamines amounts to 82. 3…”
mentioning
confidence: 99%
“…Источниками загрязнения почвы являются химические вещества и микроорганизмы, присутствие которых изменяет физические, химические и биологические свойства почвы, что приводит к снижению плодородия почвы [9]. Попав в почву или грунтовые воды, данные вещества способны не только оказывать токсическое воздействие, но и накапливаться как в почве, так и в воде [6,11,13].…”
unclassified
“…Попав в почву или грунтовые воды, данные вещества способны не только оказывать токсическое воздействие, но и накапливаться как в почве, так и в воде [6,11,13]. Контроль уровня загрязнения атмосферного воздуха осуществляется с помощью дискретных измерений разовых концентраций загрязняющих веществ с интервалом времени 20-30 мин, а также путем непрерывного отбора проб в течение суток [9,14]. В результате чего определяются -максимальная разовая Cмр и среднесуточная Cсс концентрации загрязняющих веществ [23].…”
unclassified
See 1 more Smart Citation